Consistency requirements of distributed shared memory for Lamport's bakery algorithm for mutual exclusion - Brzezinski, J.; Wawrzyniak, D. (Parallel and Distributed Processing: Proceedings of the 8th Euromicro Workshop, Rhodos, Greece, 2000, 2000)
As is well known Lamport's Bakery algorithm for mutual exclusion of n processes is correct if a physically shared memory is used as the communication facility between processes. An application of weaker consistency models (e.g. causal, processor, PRAM), available in replicated distributed shared memory (DSM) systems appealing due to possible performance improvement may imply incorrectness of the algorithm. It raises consistency requirement problem, a problem of finding weaker consistency models of DSM that is sufficient for the algorithm correctness. In this paper, consistency requirements of distributed shared memory for Lamport's Bakery algorithm for mutual exclusion of n processes are considered It is proven that the algorithm is correct with a consistency model resulting from a combination of sequential consistency and one of the weakest consistency models, PRAM, without explicit synchronisation. The combination is achieved by specifying the consistency model with write operations on shared locations.